Bioethics and Hereditary Genetic Modifications - Kaludjerovic, Zeljko (Conatus - Journal of Philosophy, 2019)
Significant breakthroughs in genetic research promoted by the human genome project, advances in molecular biology and new reproductive technologies have improved the understanding and the possibility of genetic interventions as a potential medication for diseases caused by differentiated disorders, especially those that originated in irregularities in individual genes. The progress achieved in contemporary studies has created the likelihood that the man has the technical capacity to modify the genes that will be transmitted to the next generations as well. These are the so-called hereditary genetic modifications, i.e. any biomedical interventions which could be expected to transform the genome which a person could transfer to their offspring. The author analyses in this paper why even the hints of transformations of genes that will be passed on to future generations cause deep bioethical, theological, legal and political debates and controversies. He also believes that in the era of rapid strengthening of the social and technical and technological effects of science, it is very important that scientists, in their perceptions and insights, which particularly in the field of humanities, do not have the character of value beliefs, do not go below the achieved civilization standards of ethical and moral culture and to reflect on different themes with due care and awareness of the dilemmas that they can encounter in their professional work. An adequate interdisciplinary, multidisciplinary and pluriperspective approach, as well as the awareness of the essential compatibility of scientific freedom and responsibility, should ultimately result in a different and more sophisticated attitude of the scientists themselves to the possibilities of their own discipline and the significance of its effects.